IJTIHAD HAKIM PENGADILAN AGAMA PADA PERKARA POLIGAMI - Ashabul Fadhli; Fathur Rahmi (Institut Agama Islam Negeri Batusangkar, 2020)
This study discuss about the ijtihad of the Religious Court Judges in providing legal considerations on cases of polygamy permit applications. Every decision on a polygamy permits that granted or not granted proves that there are efforts and hard work of judges in realizing and even interpreting primary and secondary sources of law in the trial process. One of the copies of the case the writer found the Judge giving strict consideration between the necessity referring to the statutory basis or to the basis of fiqh. As a legal research, this research carries out library research using the juridical-normative approach. This study takes data from a copy of the case in the Supreme Court's decision3 thematically. The results of this study indicate that the judge's Ijtihad in setting aside the primary legal basis and prioritizing fiqh considerations, even the opinion of Islamic law experts, aims to attract the benefit of the applicant's household. This finding confirms that the judge's ijtihad has an important role in producing legal decisions.